Condition-based maintenance policies for a multi-unit deteriorating system subject to shocks in a semi-Markov operating environment. Issue Volume 32:Issues 3(2020) (2nd July 2020) - Mahmoodi, Safieh; Hamed Ranjkesh, Somayeh; Zhao, Yiqiang Q.
Abstract: In this paper, we consider k out of n identical parallel unit systems experiencing deterioration due to random shocks in semi-Markov environments. It is assumed that the occurrence rate of random shocks and the corresponding failures probability are both affected by dynamical environment conditions. We discuss how the semi-Markov environment process can be converted to a Markov process. The systems are maintained through inspections and replacements under some new maintenance policies. The long-run availability and the average cost of the proposed systems are formulated. Finally, we illustrate our results using numerical examples and simulations.